Analyzing Biology Books Content in Shades of Sustainable Development Dimensions - Al-Maamary, Hind Mohammed; Al-Muzainy, Tahani AbdulRahman (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed at disclosing the range of the availability of the sustainable development dimensions in the content of Biology books taught to high school students, where the study community and the sample consists of the biology books (Syllabus System) and it’s four books. To achieve the objectives of this study, the researcher used the descriptive approach in content analyzing style, as well as building a list of the dimensions of the sustainable development that needs to be provided in high school’s Biology books and then turning this list into content analyzing card that includes (36) sub-factors sectioned into three major dimensions as follows: (social dimension, environmental dimension, economical dimension). The study concluded the following results: The sustainable development dimensions inclusion in high school’s Biology books reached (42.7%) and a medium degree inclusion. The social dimension inclusion in high school’s Biology books reached (70.6%) and a high degree inclusion. The environmental dimension inclusion in high school’s Biology books reached (45.8%) and a medium degree inclusion. The economical dimension inclusion in high school’s Biology books reached (11.8%) and a very low inclusion rate. In the shadows of the results, the researcher recommended paying more attention to the neglected dimensions of the sustainable development and including them in Biology books as well as reconsidering the possibility of including sustainable development dimensions in high schools Biology books while maintaining balance in including them.